2019
DOI: 10.3390/w11040668
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Effect on Spatial and Temporal Consistency of the New GPM-Based IMERG-v5 and GSMaP-v7 Satellite Precipitation Estimates in Brazil’s Central Plateau Region

Abstract: This study assesses the performance of the new Global Precipitation Measurement (GPM)-based satellite precipitation estimates (SPEs) datasets in the Brazilian Central Plateau and compares it with the previous Tropical Rainfall Measurement Mission (TRMM)-era datasets. To do so, the Integrated Multi-satellitE Retrievals for GPM (IMERG)-v5 and the Global Satellite Mapping of Precipitation (GSMaP)-v7 were evaluated at their original 0.1° spatial resolution and for a 0.25° grid for comparison with TRMM Multi-satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 54 publications
(89 reference statements)
3
21
1
Order By: Relevance
“…Compared to the daily and monthly estimates of 3B42V7, both IMERG products exhibited considerable enhancements in CC, RMSE, POD, and CSI. Such enhancements in GPM-based products were also reported in Singapore [35], Pakistan [11], Myanmar [40], Brazil [51], and China [39]. Improvements in the key performance measures of both IMERG products might be associated with improvements in the spatiotemporal resolution.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Compared to the daily and monthly estimates of 3B42V7, both IMERG products exhibited considerable enhancements in CC, RMSE, POD, and CSI. Such enhancements in GPM-based products were also reported in Singapore [35], Pakistan [11], Myanmar [40], Brazil [51], and China [39]. Improvements in the key performance measures of both IMERG products might be associated with improvements in the spatiotemporal resolution.…”
Section: Discussionmentioning
confidence: 61%
“…Previously, several studies have reported the performance of TRMM-and GPM-based precipitation products in different topographic and climatic conditions [7,11,31,34,51,[59][60][61][62]. Most of these studies concluded that the accuracy of precipitation retrieval algorithms used in the GPM and TRMM was strongly associated with the regional climatic system and topography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high quality of the meteorological gauging stations used in this study was already ensured by the National Meteorological Information Centre (NMIC) of China [40]. Moreover, several recent studies have successfully used the daily precipitation data of selected gauges in different hydro-climatological investigations [14,[51][52][53].…”
Section: Datasetsmentioning
confidence: 99%
“…Such algorithms consider perceptible water and cloud-top temperature to derive precipitation information. Likewise, several algorithms have also been developed to convert the MW imageries, which are generally obtained from the passive microwave sensors onboard the Low-earth orbiting (LEO) satellites, to precipitation rates using the information of cloud profile and atmospheric constituents [14]. Precipitation information derived from IR (with high spatiotemporal resolution) and MW (with high precision and relation with rainfall) satellite imageries are often blended to provide improved information of precipitation [15].…”
Section: Introductionmentioning
confidence: 99%